Evaluating fan value : a multi-dimensional approach to sports marketing - Homrich, Marcelo de Freitas (2024)
This dissertation investigates the concept of Customer Engagement Value (CEV) within sports marketing, focusing on professional soccer clubs in Brazil—the nation's primary sport, attracting millions of fans and substantial investment annually. This research proposes a revised framework to more accurately measure and leverage the multifaceted contributions of sports fans. Traditional metrics, such as direct revenue and attendance figures, often overlook the emotional, social, and informational exchanges that fans contribute, which extend beyond financial transactions. This research addresses this gap by applying the CEV framework to sports marketing for the first time, more thoroughly assessing fan value. The study unfolds through three papers. The first lays the theoretical groundwork by contrasting the unique value dynamics in sports with other sectors, advocating for a tailored valuation approach. The second paper extends this theory to practical measurement techniques, focusing on soccer fans' loyalty and emotional engagement. The third empirically assesses these concepts through interviews with sports executives and academics, highlighting professional soccer's unique contributions and valuation challenges. Findings suggest that sports fans provide significant nontransactional value that conventional metrics overlook. Sports organizations can foster more profound and profitable fan engagement by effectively measuring and integrating these dimensions into marketing strategies, promoting organizational growth and competitive advantage. The dissertation concludes that applying a CEV framework can transform sports marketing practices, advocating a paradigm shift towards more inclusive and comprehensive fan valuation models. This dissertation significantly contributes to sports marketing literature by offering a framework for understanding and leveraging the full spectrum of fan engagement. It promotes a more strategic and nuanced approach to fan interaction and value assessment.